Angiographic Findings in Unstable Angina and Prediction of 1-Year Risk of Recurrent Acute Coronary Syndrome or Death: A Nationwide Machine Learning Study - Råmunddal, Truls; Rawshani, Araz; Redfors, Björn; Petursson, Petur; Angerås, Oskar; Hirlekar, Geir; Ioanes, Dan; Odenstedt, Jacob; Dworeck, Christian; Völz, Sebastian; et al. (Cardiology and Cardiovascular Medicine, 2023)
Background: We studied whether machine learning could predict survival, risk of future acute coronary syndrome (ACS) and coronary angiographic (CAG) findings in patients with unstable angina (UA). We also studied whether high-sensitivity troponin levels within normal range can predict the presence of obstructive coronary lesions, risk of future ACS and death. Methods: We used the SWEDEHEART registry to include patients admitted to the coronary care unit due to chest pain, with normal highsensitivity cardiac troponin T or I (hs-cTnI, hs-cTnT), who underwent CAG and did not receive a final diagnosis of acute myocardial infarction (AMI). We studied CAG findings on segmental level, developed machine learning models predicting the risk of ACS or death within 1-year, and angiographic findings. The latter model predicted CAG resulting in interventions (any) or eliciting further assessments after CAG. Models for ACS and death included 130 candidate predictors and models for angiographic findings included 110 predictors. Results: We included 9’314 patients; 1-year rate of death was 0.9% (n=78) and ACS was 2.7% (n=251). A total of 5455 (61.5%) of CAG resulted in no intervention and no further assessment afterwards, with 40% without significant stenosis. There was a strong association between hscTnI (within normal range) and severity of coronary atherosclerosis; e.g 32.4% in patients with hs-cTnI 26-35 ng/L had >50% stenosis in segment 6, as compared with 12.6% in those with hs-cTnI 0-5 ng/L. All segments displayed similar associations with troponin levels. Among 17 predictors for atherosclerosis, hs-cTnI was the strongest predictor of having >50% stenosis in the left anterior descending artery (LAD). Mortality increased at hs-cTnI levels above 10 ng/L for men, but not women. Age and sex adjusted hazard ratio for hs-cTnI 25-35 vs hs-TnI 0-5 was 5.73 (2.14- 15.35) for 1-year mortality. No association was noted for hs-cTnT. The strongest predictors of 1-year mortality were C-reactive protein, body mass index, estimated glomerular filtration rate. Conclusion: Troponin levels within normal range exhibit a strong association with obstructive CAD and survival.